Evaluation of the ASSIGN open-source deterministic address-matching algorithm for allocating unique property reference numbers to general practitioner-recorded patient addresses. (2021) - Harper, Gill; Stables, David; Simon, Paul; Ahmed, Zaheer; Smith, Kelvin; Robson, John; Dezateux, Carol
No abstract available